Plaque removal efficacy of powered and manual toothbrushes under supervised and unsupervised conditions: A comparative clinical study - S Kallar; I K Pandit; N Srivastava; N Gugnani (Wolters Kluwer Medknow Publications, 2011)
The present study was undertaken to determine and compare the efficacy of manual and powered toothbrushes under supervised and unsupervised conditions in 200 school-going children between 6 and 13 years of age. Two hundred school-going children aged between 6 and 13 years were selected. Children were randomly divided into two groups of 100 in each. Group 1 children were given manual brushes, while group 2 children were given powered brushes. The groups were further divided into two subgroups, with supervised brushing in subgroup A and unsupervised brushing in subgroup B. At 3, 6, 9 and 12 weeks, plaque was recorded according to Turseky-Gilmore-Glickman modification of Quingley Hein index and oral hygiene performance index. Data were statistically analyzed. Both brushes significantly reduced the plaque accumulation, though to different degrees. Powered brushes showed significant plaque reduction as compared to the manual brushes. Supervised group of both brushes showed a greater plaque reduction.